Successful treatment of bronchiolitis obliterans organizing pneumonia with low-dose methotrexate in a patient with Hodgkin’s disease - Egerer, Gerlinde; Witzens-Harig, Mathias; Spaeth, A.; Breitbart, Andreas; Möller, Peter; Goldschmidt, Hartmut; Ho, Anthony Dick (Oncology, 2001)
Bronchiolitis obliterans organizing pneumonia (BOOP) is a rare disease, which is histopathologically defined by the presence of granulation tissue in the bronchioles, alveolar ducts and alveoli leading to plugging of the bronchiolar and alveolar lumen. BOOP is considered as a nonspecific response to many types of lung injury, including drugs, radiation, an underlying hematologic malignant neoplasm, autoimmune diseases, bacterial or virus infection, or an underlying lung disease, or occurs idiopathically. BOOP is mainly treated with corticosteroids, which induce a rapid clinical improvement. A frequent problem is relapse of disease when corticosteroid dosage is tapered off. We present the case of a 20-year-old patient with Hodgkin’s disease developing BOOP after chemotherapy (COPP/ABVD) and irradiation. Initially, she responded well to corticosteroids, but relapsed when medication was discontinued. Complete remission of BOOP was achieved by long-term treatment with low-dose methotrexate (5-20 mg/week, i.v.).
Gesehen am 21.12.2021